Considering the Appropriateness of the Verses of the Holy Quran Based on the Principle of Cooperation of Grice - Gholam Abbas Saeedi (آموزه‌های قرآنی, 2012)
Enemies have raised the issue of the disproportion and lack of coherence between the verses of the Quran from the time of the Prophet (PBUH). In the recent times, mercenary orientalists have also tried, in their opinion, to disrupt the rhetoric of the revelation. The principle of collaboration that proposed by Grice as a theory of linguistics to explore texts and considering the quality of sharing and receiving messages and producing  and getting the implications of the text, as well as discussing and showing the aspects of the literature of the text, has a very high efficiency. Utilizing the principle of collaboration of Grice, this article has looked at the proportion of the verses of the Quran and tried to offer a linguistic and rhetorical justification for the apparent disproportion of the verses of the Holy Quran.